STFM Behavioral Science/Family Systems Educator Fellowship: Evaluation of the First 4 Years. - Gorski, Victoria; Taylor, Deborah A.; Fletcher, Jason; Burge, Sandra K. (Family Medicine)
Background: The discipline of family medicine has long valued the behavioral sciences. Most residency training programs employ a clinical psychologist, social worker, or family therapist to deliver behavioral science curriculum to their residents. However, the cultures and content of training for behavioral sciences and medical professions are quite different, leaving the lone behavioral scientist feeling professionally isolated and unprepared to translate knowledge and skills into tools for the family physician. In response to this need, a group of family medicine educators developed an STFM-sponsored fellowship for behavioral science faculty. The goals of the program were to improve fellows' understanding of the culture of family medicine, provide a curricular toolbox for the behavioral sciences, promote scholarship, and develop a supportive professional network.Methods: Senior behavioral science faculty at STFM developed a 1-year fellowship program, featuring "classroom learning" at relevant conferences, mentored small-group interactions, and scholarly project requirements. Achievement of program goals was evaluated annually with pre- and post-fellowship surveys.Results: From 2010 to 2014, 59 fellows completed the program; most were psychologists or social workers; two thirds were women. One month after graduation, fellows reported significant increases in understanding the culture of medicine, improved confidence in their curricula and scholarship, and expanded professional networks, compared to pre-fellowship levels. The program required many hours of volunteer time by leaders, faculty, and mentors plus modest support from STFM staff.Conclusions: Leaders in family medicine education, confronted by the need for inter-professional development, designed and implemented a successful training program for behavioral science faculty.